Patient‐related and ENT‐related predictive factors based on the pain experienced during flexible nasendoscopy. (3rd January 2014) - Seccia, Veronica; Dallan, Iacopo; Massimetti, Gabriele; Segnini, Giovanni; Navari, Elena; Fortunato, Susanna; Bajraktari, Arisa; Lenzi, Riccardo; Muscatello, Luca; Sellari‐Franceschini, Stefano
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis The objective was to explore the role of specific patient‐related and operator‐related factors in pain perception during flexible laryngoscopy, which is one of the most common ENT procedures. Study Design Monocentric, randomized, individual prospective study. Methods A total of 532 patients (145 men and 387 women), without any relevant ENT diseases, underwent laryngoscopy performed by otolaryngologists with various degrees of experience. Patient discomfort was reported using visual analog scores, and willingness to repeat the experience was also recorded. Results Statistical analysis showed that greater pain was significantly associated with female patients and female otolaryngologists, whereas the pain was less severe in the cases of experienced laryngologists and older patients. Pain plays an important role in determining the willingness to repeat the examination; in fact, patients who experienced lower levels of pain during laryngoscopy were more prone to repeat the experience. Conclusion This article explores the importance of the extrinsic factors that are related to the patient and the otolaryngologist in determining the level of pain associated with laryngoscopy. Our study indicated that laryngoscopy is generally a well‐tolerated procedure, causing little overall discomfort, but that a subgroup of patients may experience more pain than others, which may affect the patient's perspective toward undergoing a similar future experience. Our analysis may be helpful for clinicians in understanding pain perception during a routine procedure, enabling them to focus more on that subgroup of patients who are more prone to pain. Level of Evidence 1b. Laryngoscope, 124:1648–1652, 2014